DESIGN AND IMPLEMENTATION OF FTTH NETWORKS USING OPTISYSTEM SIMULATION SOFTWARE IN KOTA RAYA RESIDENTIAL COMPLEXES - Putra, Syafarifqi Falih; Tjahjamooniarsih, Neilcy; Marpaung, Jannus (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
FTTH is an optical-based access media technology that can accommodate high-speed bandwidth and supports broadband services such as Video, Online Games, HD TV, and VoIP, FTTH itself has several technologies, namely GPON, EPON, and XPON. This research will carry out area design and mapping in the Kapur Village area which will be recommended to the provider, this research will simulate the network configuration that has been created using an optisystem that will display power transmit values as well as BER and Q-Factor graphs, this research will also carry out mapping area for placement of ODC, ODP, pole and cable lines starting from the STO to the customer. The feasibility parameters are the Power Link Budget and Rise Time Budget as well as BER and Q-Factor for optical network performance simulated on Optisystem. The simulation obtained a Prx value of -21 dBm, manual calculation of the total attenuation on the farthest fiber optic link was found to be 23.035 dB. Meanwhile, the Rise Time Budget value obtained for t_sist is 0.254594 ns and the value obtained T_r is 0.2917 ns. For the BER parameter performance resulting from the simulation, the largest value was 7,13x10^(-22) and the lowest Q Factor was 8.83409